Influence of submarine groundwater discharge on the nutrient dynamics of a fringing-reef lagoon - Zoe Ruben; Dorina Murgulet; Cody V. Lopez; Ismael Marino-Tapia; Arnoldo Valle-Levinson; Kathleen E. Matthews (Journal of Hydrology: Regional Studies)
Study region: This study investigates nutrient distribution and flux dynamics in a coral reef lagoon in Quintana Roo, Mexico, located on a permeable limestone coast of the Mesoamerican Barrier Reef System. Study Focus: Emphasis is placed on submarine groundwater discharge (SGD) as a crucial contributor to nutrient pathways, including ammonium (NH4+), nitrate and nitrite (NOx-), hydrogen silicate (HSiO3-), hydrogen phosphate (HPO42-), and urea. Inputs vary with SGD magnitudes and sources and by proximity to active spring discharges. Groundwater multi-tracer analysis and multiple linear regression identify 226Ra as explaining NH4+ variability due to long-term groundwater processes, while 223Ra predicts NOx-, HSiO3-, and urea due to short-term inputs. No significant relationship was found between HPO42- and any radium isotope, indicating complex behavior in coastal karst aquifers. New hydrological insights for the region: The findings highlight complex nutrient dynamics in coastal karst settings, with SGD-derived fluxes primarily consisting of dissolved inorganic nitrogen (DIN) and HSiO3-. Although lower in concentration, HPO42- and urea fluxes are significant compared to other karst environments. Radium isotopes distinguish between short-term and long-term, as well as new and recycled nutrient inputs. Groundwater inputs transport fresh nutrients to healthier reefs, whereas processed, recycled inputs were detected near degraded reefs. These insights are essential for understanding global nutrient cycles and coral health, particularly in the context of global change and anthropogenic disturbances affecting coral reef ecosystems.